Assessment Of Beneficiary Response About Immunization and Health Services Provided at Anganwadi Centers of Jabalpur District - Tyagi, Asha Ram; Pradhan, Sambit (National Journal of Community Medicine, 2015)
Introduction: The availability and acceptability of immunization and health services are crucial for protection and maintaining the health of children, nursing mother and adolescent girls. Therefore their positive response and satisfaction make the programme successful. Material and Methods: A cross sectional study was conducted using multistage random sampling technique during April 2011 to March 2012 in rural and urban each ICDS Projects of Jabalpur District. Se- condly 25 Anganwadies each from rural and urban were randomly selected. Lastly 10 beneficiaries as despondence response recorded by house to house visit. The data was analyzed in MS excel. Results: Beneficiaries 70.8% urban and 67.6% rural were satisfied with immunization services and 66.4% urban & 50.8% rural respon- dents agreed for availability of drugs at Anaganwadi centres. 21.6% rural, 16.4% urban reported health checkup. Heath education by 81.2% rural, 67.2% urban respondents. Work satisfaction reported 75.6% rural, 58.8% urban. All the rural respondents agreed to good attitude of Anganwadi workers. The referral services was reported available by 36%. Conclusion: A mix response was recorded. Health education and work of Anagnawadies were reported satisfactory by rural beneficia- ries. Health services seen better in rural areas whereas immunization in urban Anganwadies.